Mutual fund volatility timing and management fees - Giambona, Erasmo; Golec, Joseph (Journal of Banking & Finance, 2009)
This paper shows that compensation incentives partly drive fund managers’ market volatility timing strategies. Larger incentive management fees lead to less counter-cyclical or more pro-cyclical volatility timing. But fund styles or aggregate fund flows could also account for this relation; therefore, we control for them and find that the relation between fees and volatility timing still holds. Results show that less aggressive fund styles are associated with pro-cyclical volatility timing, and that volatility timing and flow timing are negatively related. We also find that pro-cyclical timing mostly improves funds’ average excess returns, Sharpe ratios, and alphas.